THE ROLE OF BUSINESS CAPITAL AND BUSINESS ASSISTANCE OF SAVE AND LOAN COOPERATIVES TOWARDS INCREASING MICRO AND SMALL BUSINESSES IN HERLANG SUB-DISTRICT, BULUKUMBA REGENCY - Achsanuddin UA, Anur; Fitrianti, A Nur; Irmayanti, Irmayanti (Jurnal Ekonomi Balance, 2019)
The role of venture capital and business assistance for savings and loan cooperatives thanks to the increase in micro and small business in herlang subdistrict, Bulukumba Regency. Thesis of economics study program for the development of the faculties of economics and business at the muhammadiyah university of Makassar, Guided by supervisor I Edi Jusriadi and supervisor II Warda. The purpose of this research was to know the role of venture capital and business assistance for savings and loan cooperatives thanks to the increase (UMK) in lion village, Herlang district, Bulukumba Regency. The type of data used is qualitative and quantitative data. The data source used is secondary data. The data source used is secondary data. The analytical method used is a quantitative analysis method, namely the method of multiple linear regression analysis, f test (simultaneous), and t test (partial).  Where the calculation of multiple linear regression Y = 11,392 + 0,660 MU + 0,750 PU + e, obtained a partial test that is the role of business capital and business assistance have a significant positive effect on business improvement. From the result of the simultaneous test, the role of venture capital and business assistance have a significant positive effect on the increase (UMK) in the lion village, Herlang district, Bulukumba regency. Thus the hypothesis is accepted